2015
DOI: 10.1159/000375167
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endovascular Reconstruction of a Recurrent Giant Middle Cerebral Artery Aneurysm with Multiple Telescoping Flow Diverters in a Pediatric Patient

Abstract: Intracranial aneurysms of the pediatric population are rare, but giant fusiform aneurysms (GFAs) of the middle cerebral artery (MCA) are common within this cohort of patients. These aneurysms are difficult to treat and often require advanced microsurgical skills, as they are usually not amenable to direct clipping. Here, we report the successful treatment of a recurrent GFA of the MCA with three telescoping Pipeline Embolization Devices 6 months after attempted clip reconstruction in a pediatric patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Pediatric patients also show different pathogenesis, demographics, and anatomical features for aneurysms, including male predominance, higher incidence in the posterior circulation, and a greater incidence of large and giant aneurysms. The initial presentations of most unruptured aneurysms in the pediatric population include headache, seizure, and mass effect [3]. Aneurysms in this population are often not amenable to direct microsurgical clip reconstruction techniques due to the predominance of unfavorable locations for surgical access [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients also show different pathogenesis, demographics, and anatomical features for aneurysms, including male predominance, higher incidence in the posterior circulation, and a greater incidence of large and giant aneurysms. The initial presentations of most unruptured aneurysms in the pediatric population include headache, seizure, and mass effect [3]. Aneurysms in this population are often not amenable to direct microsurgical clip reconstruction techniques due to the predominance of unfavorable locations for surgical access [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few case reports on the use of flow diverters in the pediatric population. [2][3][4][5][6][7][8][9][10][11] In this retrospective study, we report our experience with of flow diverters in 5 children with intracranial aneurysms and 2 children with carotid cavernous fistulas (CCFs). Through a review of our patient data and the relevant literature, we also summarize the current antiplatelet regimens used for children undergoing cerebrovascular interventions involving the placement of stents and flow diverters.…”
mentioning
confidence: 99%
“…Analyzing the 35 cases reported in the literature in which there is a somewhat detailed description of the placement of cerebral vascular scaffolds in children, we found that antiplatelet administration for endovascular treatment was extremely variable (On-line Table 2). [2][3][4][5][6][7][8][9][10][11]25,[31][32][33][34][35][36][37][38][39][40][41][42][43] There are neither guidelines published on antiplatelet therapy (APT) in children with cerebrovascular diseases 25 nor conclusive trials on pediatric APT regimens. 44,45 Weight-based dose calculations extrapolated from an adult dosing of 75 mg per day are not only misleading but also may lead to lifethreatening consequences.…”
mentioning
confidence: 99%
“…12,15,17,29 As in adults, the treatment of intracranial aneurysms in children can involve microsurgical clip ligation, wrapping, and endovascular treatment including flow diversion, coiling, and embolization of the aneurysm and parent vessel. 1,13,14,20,30,34,37 The rate of new SAH is higher in both adults and children with a previous aneurysm rupture than in the general population; it occurs as a result of recurrent aneurysms as well as de novo aneurysm formation. 4,35,39 In pediatric patients with a mean follow-up of 4-6 years, 11,15,30 a 13%-23% cumulative rate of de novo aneurysm formation has been reported.…”
mentioning
confidence: 99%
“…1,13,14,20,30,34,37 The rate of new SAH is higher in both adults and children with a previous aneurysm rupture than in the general population; it occurs as a result of recurrent aneurysms as well as de novo aneurysm formation. 4,35,39 In pediatric patients with a mean follow-up of 4-6 years, 11,15,30 a 13%-23% cumulative rate of de novo aneurysm formation has been reported.…”
mentioning
confidence: 99%